MENELUSURI MAKNA KEBAIKAN PADA PENAFSIRAN KATA AL-BIRR DAN IHSAN DALAM AL-QUR’AN SERTA AKTUALISASINYA DALAM KEHIDUPAN - Mubasirun Mubasirun (Institut Keislaman Abdullah Faqih Gresik, 2022)
Abstract: The words birr and ihsan in various dictionaries and translations of verses of the Qur'an have the same meaning, namely goodness. While the Qur'an uses words that designate the meaning of goodness with several terms, namely ihsan, birr, khair, ma'ruf, hasan, toyyib, jayyid. Among the various words that designate the meaning of goodness used in the Qur'an, the words birr and ihsan play important terms in the structure of linguistic concepts in the Qur'an which are often not understood by many people. In exploring the meaning of the words birr and ihsan, the basic, relational, paradigmatic and simantic meaning approaches are used. The basic meaning is the meaning attached to each word itself. Relational meaning is something connotative that is given and added to the existing meaning by placing the word in a special position, being in a different relationship with all words. From the results of the search, it was found that the words birr and ihsan have the basic meaning of